Preparation method of anode gas diffusion layer porous electrode

By coating a coating solution made of manganese salt on the porous titanium matrix, and applying noble metal compounds on its surface by immersion, the deposition and easy detachment of the porous electrode active material of the anode gas diffusion layer is solved. The problem of the electrode improves the activity and stability and adapts to strong airflow and liquid impact under high current density.

CN119392282APending Publication Date: 2025-02-07XIAN TAIJIN NEW ENERGY & MATERIALS SCI TECH CO LTD

Patent Information

Application Number
CN202411349520.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

When the existing anode gas diffusion layer porous electrode is coated with the active layer on the surface, the active substance is deposited in the pore structure in large quantities, reducing the utilization rate of the active substance, affecting the pore structure of the porous transport layer, resulting in poor gas-liquid transmission and easy active substances. Problems such as shedding affect electrode activity and stability.

Method used

The porous titanium matrix is ​​coated with a coating solution made of manganese salt to form a porous manganese dioxide/Ti electrode, and noble metal compounds are coated on the surface through the impregnation method to increase the distribution area of ​​the active layer and improve the stability of the electrode.

Benefits of technology

By preparing the porous manganese dioxide support layer, the impact effect of water flow and air flow on the proton exchange membrane is weakened, the transmission capacity of oxygen evolution intermediates is improved, the impact of strong air flow and liquids under high current density is improved, and the distribution of precious metal compounds is improved Area enhances the activity and stability of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392282A_ABST
    Figure CN119392282A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of a porous gas diffusion layer in an electrolytic cell, and particularly relates to a preparation method of an anode gas diffusion layer porous electrode, which is characterized in that a manganese dioxide / Ti electrode with a porous structure is prepared by coating and sintering a coating solution A containing manganese salt on a titanium substrate. The porous manganese dioxide supporting layer serves as micropore extension of the porous transmission layer, the impact effect of water flow and air flow on the proton exchange membrane is weakened, transmission of an oxygen evolution intermediate in the hydrogen production process is facilitated, and the proton exchange membrane is suitable for strong air flow and liquid impact under high current density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparing a porous gas diffusion layer in an electrolytic cell, and in particular relates to a method for preparing a porous electrode of an anode gas diffusion layer. Background Art

[0002] In a PEM hydrogen production electrolyzer, a single hydrogen production chamber includes an anode current collector, an anode gas diffusion layer, a catalyst-coated membrane electrode, a cathode gas diffusion layer, and a cathode plate; wherein the gas diffusion layer plays the role of supporting the catalyst layer, collecting current, conducting gas, and discharging the reaction product water. When the electrolysis reaction is carried out in the PEM electrolyzer, in order to improve the efficiency of hydrogen production and reduce the cost of hydrogen production, the hydrogen production electrode is often required to withstand a larger current density and have a lower precious metal load. However, due to the presence of a porous structure, the gas diffusion layer on the anode side cannot be fully in contact with the anode iridium-based catalyst coated on the proton exchange membrane, resulting in failure of local active sites. Therefore, most catalysts are coated on the porous gas diffusion surface to form a gas diffusion layer electrode. Although a larger specific surface area is formed, the porous structure also leads to unnecessary waste of precious metal oxide slurry, and at the same time affects the pore structure of the porous transport layer to transport gas, affecting the electrode activity and stability. For example, in the Chinese invention patent with publication number CN114204049A, the catalyst is directly sprayed on the gas diffusion layer to form a catalyst-resin gradient structure, which is applied to the fuel cell membrane electrode. However, an overly thick coating will cover the pore structure of the gas diffusion layer, which is not conducive to gas transmission. In the Chinese invention patent with publication number CN118073578A, a nanoarray is grown in situ on the surface of the gas diffusion layer using a three-electrode system for solid oxide fuel cells; however, the nanoarray structure is not suitable for proton exchange membranes with low mechanical strength, and this method cannot be mass-produced.

[0003] Therefore, when the active layer is coated on the surface of the existing anode gas diffusion layer porous electrode, a large amount of active substances are deposited in the pore structure, which reduces the utilization rate of the active substances and affects the pore structure of the porous transport layer, causing problems such as poor gas-liquid transmission and easy falling off of the active substances, affecting the electrode activity and stability and limiting the scope of application. Summary of the invention

[0004] In order to solve the above problems, the purpose of the present invention is to provide a method for preparing a porous electrode for an anode gas diffusion layer, by coating a coating liquid made of manganese salt on a titanium substrate to obtain a manganese dioxide / Ti electrode with a porous structure, which is beneficial to the transmission of oxygen evolution intermediates in the hydrogen production process and adapts to strong airflow and liquid impact under high current density.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a porous electrode of an anode gas diffusion layer, wherein the anode gas diffusion layer uses porous titanium as a matrix, and the preparation method comprises the following steps:

[0007] Step 1, substrate pretreatment: degreasing, sandblasting, acid etching, and then cleaning and drying the porous titanium substrate;

[0008] Step 2, preparing coating liquid A: electrolyzing the high molecular polymer and dispersing it in a solvent, adding manganese salt and an oxidant after ultrasonic treatment, and continuing low-temperature ultrasonic treatment to obtain coating liquid A;

[0009] Step 3, preparing active liquid B: dissolving the noble metal salt in an organic solvent to form active liquid B;

[0010] Step 4, uniformly coating the coating liquid A prepared in step 2 on the porous titanium substrate pretreated in step 1, and continuing to coat after drying until the coating liquid A forms a desired thickness on the titanium substrate, and obtaining a manganese dioxide / Ti electrode with a porous structure after drying and calcining;

[0011] Step 5, immersing the porous manganese dioxide / Ti electrode obtained in step 4 in the active solution B prepared in step 3, taking it out and drying it, and then calcining it. After immersing and sintering for multiple times, a porous manganese dioxide / Ti electrode with dispersed precious metals is obtained.

[0012] Preferably, in step 2, the high molecular polymer is any one or a combination of polytetrafluoroethylene, naphthol, perfluorosulfonic acid, poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid; the oxidant is any one of ammonium persulfate, ammonium bisulfite, tetrabutylammonium hydroxide, tetramethylammonium hydroxide, etc.

[0013] Preferably, in step 2, the manganese salt is one or a combination of two of manganese nitrate, manganese dioxide nanosheets, and manganese sulfate.

[0014] Preferably, in step 2, the solvent is a mixture of water and an alcohol solvent, and the alcohol solvent is preferably n-butanol.

[0015] Preferably, the volume ratio of water to n-butanol is 1:2.

[0016] Preferably, in the coating liquid A, the concentration of manganese salt is 30% to 50%, the concentration of high molecular polymer is 0.5 to 5% of the concentration of manganese salt, and the molar ratio of the oxidant to manganese ions is 0.5 to 1.

[0017] Preferably, the noble metal salt in step 3 is one or a combination of iridium trichloride, chloroiridic acid, anhydrous ruthenium chloride, potassium chloroiridate, and chloroplatinic acid; the organic solvent is n-butanol; and the concentration of the active solution B is 0.1 mmol / L.

[0018] Preferably, step 4 specifically includes the following process: drying the porous titanium substrate coated with coating liquid A at 80°C, repeating the above steps of coating and drying multiple times until the coating liquid A is coated on the surface of the titanium substrate and the sintered manganese dioxide layer has a thickness of 0.5 to 2 μm. After the last drying, the temperature is increased to 400 to 600°C at a rate of 1°C / min, and calcined for 1 to 3 hours to obtain a manganese dioxide / Ti electrode with a porous structure.

[0019] Preferably, step 5 specifically includes the following process: immersing the porous manganese dioxide / Ti electrode in the precious metal active solution B for 20 minutes, taking it out and drying it, and then calcining it at 350-550°C for 15 minutes; after immersion and sintering 5-10 times, a porous manganese dioxide / Ti electrode with dispersed precious metals is obtained.

[0020] Preferably, the porous titanium matrix comprises a porous material formed by bonding one or more of titanium mesh, titanium fiber felt, and porous titanium.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The present invention utilizes the properties of manganese dioxide, which has good acid resistance and good electrical conductivity, to prepare a porous manganese dioxide support layer on the surface of a titanium substrate. The presence of the porous manganese dioxide support layer serves as a micropore extension of a porous transmission layer, which weakens the impact of water flow and air flow on the proton exchange membrane, is beneficial to the transmission of oxygen evolution intermediates in the hydrogen production process, and adapts to strong air flow and liquid impact under high current density;

[0023] 2. The noble metal compound is coated on the surface of the porous manganese dioxide support layer by an immersion method. The porous manganese dioxide support layer serves as a direct conductive layer, which increases the distribution area of ​​the active noble metal compound, makes the active layer less likely to fall off, and improves the electrode activity and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a surface morphology of the anode gas diffusion layer electrode prepared in Example 1 of the present invention.

[0025] Figure 2 This is a comparative curve diagram of the electrolysis performance of the anode gas diffusion layer electrodes prepared in Examples 1 and 2 of the present invention and the anode gas diffusion layer of Comparative Example 1 in a PEM electrolyzer. DETAILED DESCRIPTION

[0026] The present invention provides a method for preparing a porous electrode of an anode gas diffusion layer, wherein the anode gas diffusion layer uses porous titanium as a substrate, and the preparation method comprises the following steps:

[0027] Step 1, substrate pretreatment: degreasing, sandblasting, soaking in 10% dilute hydrochloric acid for 15 minutes for etching, cleaning and drying; the porous titanium substrate includes a porous material formed by bonding one or more of titanium mesh, titanium fiber felt, and porous titanium; the titanium substrate of the present invention is preferably titanium fiber felt.

[0028] Step 2, preparing coating liquid A: electrolyzing a high molecular polymer and dispersing it in a solvent, placing the solution in an ice bath environment and performing sufficient ultrasonic treatment, then adding a manganese salt and an oxidant and continuing low-temperature ultrasonic treatment to obtain coating liquid A;

[0029] The high molecular polymer is any one or a combination of polytetrafluoroethylene, naphthol, perfluorosulfonic acid, poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid, which plays the role of dispersion and pore formation; the high molecular polymer in the embodiment of the present invention is preferably polytetrafluoroethylene and naphthol.

[0030] The oxidant is any one of ammonium persulfate, ammonium bisulfite, tetrabutylammonium hydroxide, tetramethylammonium hydroxide, etc.; the oxidant of the present invention is preferably ammonium persulfate or tetramethylammonium hydroxide.

[0031] The solvent is a mixture of water and an alcohol solvent, the alcohol solvent is preferably ethanol, and the volume ratio of water to ethanol is 1:2.

[0032] The manganese salt is one or a combination of manganese nitrate, manganese dioxide nanosheets, and manganese sulfate; in the embodiment of the present invention, the manganese salt is preferably manganese nitrate. The concentration of the manganese salt is 30% to 50%, the concentration of the high molecular polymer is 0.5 to 5% of the concentration of the manganese salt, and the molar ratio of the oxidant to the manganese ion is 0.5 to 1.

[0033] Step 3, preparing active liquid B: dissolving a noble metal salt in an organic solvent to form an iridium-based active liquid B; the noble metal salt is one or a combination of iridium trichloride, ruthenium trichloride, chloroiridic acid, anhydrous ruthenium chloride, potassium chloroiridate, and chloroplatinic acid, and the concentration of active liquid B is 0.1 mmol / L; the organic solvent is n-butanol. The noble metal salt of the present invention is preferably chloroiridic acid and / or ruthenium trichloride.

[0034] Step 4, uniformly coating the coating liquid A prepared in step 2 on the porous titanium substrate pretreated in step 1, and continuing coating after drying in an oven at 80°C, repeating the above steps of coating and drying multiple times until the coating liquid A is coated on the surface of the titanium substrate and the sintered manganese dioxide layer has a thickness of 0.5 to 2 μm. After the last drying, place it in a muffle furnace, heat it to 400 to 600°C at a heating rate of 1°C / min, and calcine it for 1 to 3 hours to obtain a manganese dioxide / Ti electrode with a porous structure;

[0035] Step 5, immerse the porous manganese dioxide / Ti electrode obtained in step 4 in the 0.1mmol / L precious metal active solution B prepared in step 3 for 20 minutes, then take it out and dry it, and then calcine it at 350-550°C in a muffle furnace for 15 minutes; after immersion and sintering 5-10 times, a porous manganese dioxide / Ti electrode with dispersed precious metals is obtained.

[0036] The present invention utilizes the good acid resistance and good electrical conductivity of manganese dioxide to prepare a porous manganese dioxide support layer on the surface of a titanium substrate. The presence of the porous manganese dioxide support layer serves as a micropore extension of a porous transmission layer, which weakens the impact of water flow and air flow on the proton exchange membrane, is beneficial to the transmission of oxygen evolution intermediates in the hydrogen production process, and adapts to strong air flow and liquid impact under high current density.

[0037] The noble metal compound is coated on the surface of the porous manganese dioxide support layer by an immersion method. The porous manganese dioxide support layer serves as a direct conductive layer to increase the distribution area of ​​the active noble metal compound, making the active layer less likely to fall off, thereby improving the electrode activity and stability.

[0038] Example 1

[0039] A method for preparing a porous electrode of an anode gas diffusion layer, wherein the anode gas diffusion layer uses porous titanium as a matrix, and the preparation method comprises the following steps:

[0040] Step 1, substrate pretreatment: titanium fiber felt is selected for degreasing and sandblasting, then immersed in 10% dilute hydrochloric acid for 15 minutes for etching, then cleaned and dried;

[0041] Step 2, preparing coating liquid A: weigh 0.145 g of naphthol, electrolyze it and disperse it in an organic solvent consisting of 2.5 ml of deionized water and 5 ml of ethanol to form a dispersion, place the dispersion in an ice bath environment and fully ultrasonically disperse it for 15 minutes, then add 1.4 g of manganese sulfate and 1.89 g of ammonium persulfate, and continue ultrasonically dispersing it for 15 minutes to obtain coating liquid A.

[0042] Step 3, preparing active solution B: accurately weigh 90 mg of chloroiridic acid and dissolve it in n-butanol solvent, stir at room temperature until completely dissolved to form 0.1 mmol / L iridium-based active solution B, and store it for later use;

[0043] Step 4, evenly apply the coating liquid A prepared in step 2 on the porous titanium substrate pretreated in step 1, and continue to apply after drying in an oven at 80°C until the coating liquid A is applied 18 times on the titanium substrate to obtain a manganese dioxide layer with a thickness of about 2 μm. Place the dried titanium substrate in a muffle furnace, heat it to 600°C at a heating rate of 1°C / min, keep it warm for 2 hours, and cool it in the furnace to obtain a manganese dioxide / Ti electrode with a porous structure.

[0044] Step 5, the porous manganese dioxide / Ti electrode obtained in step 4 is immersed in the iridium-based active solution B prepared in step 3 for 20 minutes, then taken out and dried, and then calcined in a muffle furnace at 350°C for 15 minutes; after immersion and sintering for 5 times, an iridium-dispersed porous manganese dioxide / Ti electrode is obtained. Its morphology is shown in the figure Figure 1 shown.

[0045] Example 2

[0046] A method for preparing a porous electrode of an anode gas diffusion layer, wherein the anode gas diffusion layer uses porous titanium as a matrix, and the preparation method comprises the following steps:

[0047] Step 1, substrate pretreatment: titanium fiber felt is selected for degreasing and sandblasting, then immersed in 10% dilute hydrochloric acid for 15 minutes for etching, then cleaned and dried;

[0048] Step 2, preparing coating liquid A: weigh 0.5 g of polytetrafluoroethylene, electrolyze it and disperse it in an organic solvent consisting of 2.5 ml of deionized water and 5 ml of ethanol to form a dispersion, place the dispersion in an ice bath environment and fully ultrasonically disperse it for 15 minutes, then add 1.4 g of manganese dioxide nanosheets and 0.94 g of tetramethylammonium hydroxide, and continue low-temperature ultrasonic dispersion for 15 minutes to obtain coating liquid A.

[0049] Step 3, prepare active liquid B: accurately weigh 30 mg of chloroiridic acid and 60 mg of ruthenium trichloride and dissolve them in n-butanol solvent, stir at room temperature until completely dissolved to form 0.1 mmol / L noble metal active liquid B, and store it for later use;

[0050] Step 4, uniformly coating the coating liquid A prepared in step 2 on the porous titanium substrate pretreated in step 1, and continuing to coat after drying in an oven at 80°C. The coating liquid A is coated on the titanium substrate 5 times to obtain a manganese dioxide layer with a thickness of about 0.5 μm. The dried titanium substrate is placed in a muffle furnace, and the temperature is increased to 400°C at a heating rate of 1°C / min, and the temperature is kept for 3 hours. After cooling with the furnace, a manganese dioxide / Ti electrode with a porous structure is obtained;

[0051] Step 5, the porous manganese dioxide / Ti electrode obtained in step 4 is placed in the iridium-based active solution B prepared in step 3, immersed for 20 minutes, taken out and dried, and then calcined at 550° C. in a muffle furnace for 15 minutes; after immersion and sintering 5 times, a porous manganese dioxide / Ti electrode with iridium and ruthenium binary dispersion is obtained.

[0052] Comparative Example 1

[0053] The anode gas diffusion layer porous electrode adopts commercial platinum-coated titanium felt and sprays iridium oxide catalyst on the surface.

[0054] like Figure 2The electrolysis performance curves of the anode gas diffusion layer electrodes prepared in Example 1 and Example 2 and the anode gas diffusion layer of Comparative Example 1 in a PEM electrolyzer are compared. Figure 2 We can see that: as the current density increases, the voltage of the embodiment of the present invention is lower than that of comparative example 1; the present invention prepares a porous manganese dioxide support layer on the surface of the titanium substrate as a microporous extension of the porous transmission layer, which weakens the impact of water flow and air flow on the proton exchange membrane, is beneficial to the transmission of oxygen evolution intermediates in the hydrogen production process, and adapts to strong airflow and liquid impact under high current density; at the same time, the surface of the porous manganese dioxide support layer is coated with precious metal compounds by an immersion method. The porous manganese dioxide support layer serves as a direct conductive layer to increase the distribution area of ​​the active precious metal compounds, making the active layer less likely to fall off, thereby improving the electrode activity and stability.

Claims

1. A method for preparing a porous electrode of an anode gas diffusion layer, wherein the anode gas diffusion layer uses porous titanium as a substrate, characterized in that: The preparation method comprises the following steps: Step 1, substrate pretreatment: degreasing, sandblasting, acid etching, and then cleaning and drying the porous titanium substrate; Step 2, preparing coating liquid A: electrolyzing the high molecular polymer and dispersing it in a solvent, adding manganese salt and an oxidant after ultrasonic treatment, and continuing low-temperature ultrasonic treatment to obtain coating liquid A; Step 3, preparing active liquid B: dissolving the noble metal salt in an organic solvent to form active liquid B; Step 4, uniformly coating the coating liquid A prepared in step 2 on the porous titanium substrate pretreated in step 1, and continuing to coat after drying until the coating liquid A forms a desired thickness on the titanium substrate, and obtaining a manganese dioxide / Ti electrode with a porous structure after drying and calcining; Step 5, immersing the porous manganese dioxide / Ti electrode obtained in step 4 in the active solution B prepared in step 3, taking it out and drying it, and then calcining it. After immersing and sintering for multiple times, a porous manganese dioxide / Ti electrode with dispersed precious metals is obtained.

2. The preparation method according to claim 1, characterized in that: In step 2, the high molecular polymer is any one or a combination of polytetrafluoroethylene, naphthol, perfluorosulfonic acid, poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid; the oxidant is any one of ammonium persulfate, ammonium bisulfite, tetrabutylammonium hydroxide, tetramethylammonium hydroxide, etc.

3. The preparation method according to claim 1, characterized in that: In step 2, the manganese salt is one or a combination of two of manganese nitrate, manganese dioxide nanosheets, and manganese sulfate.

4. The preparation method according to claim 1, characterized in that: In step 2, the solvent is a mixture of water and an alcohol solvent, and the alcohol solvent is preferably ethanol.

5. The preparation method according to claim 4, characterized in that: The volume ratio of water to ethanol is 1:

2.

6. The preparation method according to claim 1, characterized in that: In the coating liquid A, the concentration of manganese salt is 30% to 50%, the concentration of high molecular polymer is 0.5 to 5% of the concentration of manganese salt, and the molar ratio of the oxidant to manganese ion is 0.5 to 1.

7. The preparation method according to claim 1, characterized in that: In step 3, the noble metal salt is one or a combination of iridium trichloride, chloroiridic acid, anhydrous ruthenium chloride, potassium chloroiridate, and chloroplatinic acid; the organic solvent is n-butanol; and the concentration of the active solution B is 0.1 mmol / L.

8. The preparation method according to claim 1, characterized in that: The step 4 specifically includes the following process: The porous titanium substrate coated with coating liquid A is dried at 80°C, and the above steps are repeated for multiple times until the coating liquid A is coated on the surface of the titanium substrate and the sintered manganese dioxide layer has a thickness of 0.5 to 2 μm. After the last drying, the temperature is increased to 400 to 600°C at a rate of 1°C / min and calcined for 1 to 3 hours to obtain a manganese dioxide / Ti electrode with a porous structure.

9. The preparation method according to claim 1, characterized in that: The step 5 specifically includes the following process: immersing the porous manganese dioxide / Ti electrode in the noble metal active solution B for 20 minutes, taking it out and drying it, and then calcining it at 350-550° C. for 15 minutes; After impregnation and sintering for 5 to 10 times, a porous manganese dioxide / Ti electrode with noble metal dispersed therein is obtained.

10. The preparation method according to claim 1, characterized in that: The porous titanium matrix includes a porous material formed by bonding one or more of titanium mesh, titanium fiber felt, and porous titanium.

Citation Information

Patent Citations

  • Preparation method of membrane electrode of low-platinum-loading proton exchange membrane fuel cell

    CN114204049A

  • Gas diffusion layer electrode with high durability and application thereof

    CN118073578A

Cited By

  • Preparation method of gas transmission layer electrode with microporous layer

    CN120989649A